Edukasi Tentang Bahaya Merokok Bagi Anak - Gani Apriningtyas Budiyati; Suryati (LPPM STIKES Guna Bangsa Yogyakarta, 2021)
In Indonesia, many deaths are related to cigarette use. In addition, Indonesia is a country that uses a lot of cigarettes. The emergence of active smokers will increase the risk of passive smoking, especially in children. For this reason, education is needed, especially for caregivers about the harmful effects of smoking on children. The method used in this community service is lecture/education with leaflets delivered online. The results of this community service show an increase in 2 indicators. The indicator is able to mention harmful substances in cigarettes from 25% to 70%. While the second indicator, which states the dangers of smoking for children, increased from 60% to 70%. The conclusion of this community service is that education about the impact of smoking on children can increase the knowledge of caregivers and it is hoped that caregivers can prevent children from exposure to cigarette smoke. Suggestions for the next servant to be able to develop educational topics and educational models to increase public awareness, especially in the field of preventing smoking behavior.